A pilot study to assess superficial versus deep tissue culture in acute wounds - Prabhu, Vinod V.; Shivani, Aslam A.; Shah, Shilpa; Gore, Alka D. (International Surgery Journal, 2016)
Background:To determine whether concordance exists between superficial and deep tissue culture in isolating organisms in acute wounds. Methods: In acute wounds presenting to surgical department a superficial swab was taken and after debridement of the wound a deep tissue biopsy was taken to isolate organisms for sensitivity. Results were analyzed using z-score at p <0.05. Results: Sample size of 50 cases was studied for isolates.28 cases were non diabetic and the rest diabetics. There was a significant disconcordance of isolates in diabetics (81.8%) as compared to 21.4% in non-diabetics. Conclusions: Simultaneous swabbing and deep tissue biopsy improves the isolate detection rate in ulcers for diabetics and minimizes the under treatment risk in this group of patients. This is also true for non-diabetic ulcers as there is a possibility of disconcordance in this group too, though infrequent.